Rainfall-Runoff Simulation of Malayer Basin Using SWAT and IHACRES Models - Saeed Eskandari; Amin Toranjian (محیط زیست و مهندسی آب)
Considering the diverse landscape of rainfall-runoff models, a thorough evaluation of their capabilities and limitations is essential for the selection of an optimal model. This study aims to assess the performance of rainfall-runoff hydrological models in the Malayer watershed. In this study, Rainfall-runoff simulation was carried out using SWAT and IHACRES models and meteorological data from 2005 to 2020. The calibration and validation of the model were done using the SUFI-2 algorithm. The results of sensitivity analysis showed that the melting factor, hydraulic conductivity of soil saturation, and snowfall temperature are the most important parameters controlling the flow rate in the study area. The R2 and NS coefficients for SWAT were calculated as 0.68 and 0.65 in the calibration period and 0.63 and 0.70 in the validation period, respectively which in these results showed the SWAT model has suitable efficiency for estimating the watershed flow. Based on the simulation results of the IHACRES model, the values ​​of R2 and NS are 0.66 and 0.58 in the calibration period and 0.52 and 0.51 in the validation period, respectively. Considering that the IHACRES model simulates runoff on a daily scale, the efficiency of the model can be evaluated as acceptable.